ARCHETYPE ANALYSIS OF MAIN CHARACTERS IN THE SECRET GARDEN (2020) MOVIE BY FRANCES HODGSON BURNETT - Rifka Puspawarni; Dina Amelia (English Literature Study Program, Faculty of Arts and Education Universitas Teknokrat Indo, 2023)
The researcher uses Jung’s archetypes theory to analyze the personality of Mary Lennox and Colin Craven as the main characters in The Secret Garden (2020) movie by Frances Hodgson Burnett. Carl Jung uses archetypes to analyze the human side of personality, which is known as a term in psychology. The researcher uses a descriptive qualitative method. The results show that the characters Mary Lennox and Colin Craven have three kinds of archetypes. These results include the shadow, persona, anima, or animus. Mary's shadow is seen when she is angry because she is ignored by Martha, misunderstood by Colin, and a liar. Meanwhile, Colin's shadow is seen when he had past trauma about the stench of roses that almost killed him, and he hated his mother because she died. Second, Mary's persona is seen as a good girl who follows the rules of the house. Meanwhile, Colin's persona was seen. He was manipulating information that he had a friend. Third, Colin reveals four characteristics of anima: touchy, moody, jealous, and unadjusted. The last, there are two characteristics of the animus revealed in Mary, such as strong and brave. Keywords: anima, animus, persona, shadow, The Secret Garden (2020)